(untitled) (Medico Legal Update, 2021)
Background: Pregnancy is a physiological action that ends with pain, fear, anxiety and fear of death for the mothers. Delivery is a multi-dimensional process associated with physical, emotional, social, physiological, cultural and psychological dimensions. Objectives: To identify the preferred mode of delivery in Iraq primiparous women and factors make them chose this mode of delivery. Methodology: a descriptive/analytical cross-sectional study performed among 150 Iraqi primiparous women who attended the gynecology clinic in Baghdad teaching hospital/medical city from July to November 2019 the information regarding socio-demographical data and asking the women about the causes of this choice. Results: Total of 150 primiparous women was enrolled in the study. Majority of them preferred vaginal delivery (68.7%) while women who preferred cesarean section were (31.3%). high rate of vaginal delivery preference was seen in women because of faster recovery, easy baby bonding, fear from cesarean section and short hospital stay, while those who preferred cesarean section thought that they can avoid labor pain and fear on baby’s life. Conclusion: Majority of primiparous women interviewed in our research preferred the vaginal delivery, while the remaining women preferred the cesarean section due to lack of knowledge or fear from vaginal delivery. Doctor’s recommendation and medical advices play a major role in enhancing the awareness toward vaginal delivery.